Branded marketing events: engaging Australian and French wine consumers. Issue 2 (13th March 2017) - Altschwager, Teagan; Conduit, Jodie; Bouzdine-Chameeva, Tatiana; Goodman, Steve
Abstract : Purpose: The purpose of this paper is to introduce the term branded marketing events (BMEs), and examine the role of its experiential components as a strategic tool for the facilitation of customer brand engagement. This study examines five experiential components of BMEs at events held in Australia and France to determine their respective impact on customer brand engagement. Design/methodology/approach: Surveys were distributed to attendees of ten events by six wine brands in South Australia, and six events in five sub-regions of Bordeaux. Findings: Findings suggest that BMEs influence customers' brand engagement and brand purchase intention in both Australia and France. However, the experiential components within the events had differing effects. Australian customers were influenced by cognitive, sensorial, and relational experiences and their increased customer brand engagement strongly influenced brand purchase intention. French customers, however, required pragmatic event experiences to build brand engagement. Originality/value: Recognizing their mutual experiential and interactive foundations, this study integrates the research domains of marketing events, customer experiences and customer brand engagement, and contributes to the strategic understanding of how branded event experiences facilitate customer brand engagement.